Cardiac tamponade from anticoagulant-related spontaneous haemopericardium in a patient with ischaemic cardiomyopathy and heart failure. Issue 12 (28th December 2020) - Lefas, Alicia; Bodagh, Neil; Pan, Jiliu; Vazir, Ali
Abstract : We describe the case of an 86-year-old man with a background of severe left ventricular dysfunction and ischaemic cardiomyopathy who, having been optimised for heart failure therapy in hospital, unexpectedly deteriorated again with hypotension and progressive renal failure over the course of 2 days. Common causes of decompensation were ruled out and a bedside echocardiogram unexpectedly diagnosed new pericardial effusion with tamponade physiology. The patient underwent urgent pericardiocentesis and 890 mL of haemorrhagic fluid was drained. Common causes for haemopericardium were ruled out, and the spontaneous haemopericardium was thought to be related to introduction of rivaroxaban anticoagulation. The patient made a full recovery and was well 2 months following discharge. This case highlights the challenges of diagnosing cardiac tamponade in the presence of more common disorders that share similar non-specific clinical features. In addition, this case adds to growing evidence that therapy with direct oral anticoagulants can be complicated by spontaneous haemopericardium, especially when coadministered with other agents that affect clotting, renal dysfunction and cytochrome P3A5 inhibitors.